Switchable liquid-crystalline polymers and dendrimers based on the ferrocene-ferrocenium redox system - Deschenaux, Robert (: American Chemical Society, 2002)
We have recently demonstrated that electron transfer can be used in the ferrocene-ferrocenium redox couple to generate liq.-cryst. properties and to tune the liq.-cryst. organization. Such a behavior is of interest for the development of mol. switches. The concept is based on the fact that different intermol. interactions take place between the ferrocene units (neutral species) or the ferrocenium units (charged species). The ferrocene-based materials were oxidized with silver tosylate or silver dodecylsulfate. In case of the ferrocenium-contg. liq. crystals, the counter-anion had an influence on the thermal and liq.-cryst. properties. Therefore, the mol. organization within the liq.-cryst. assemblies could also be tuned as a function of the nature and structure of the counter-anion. [on SciFinder(R)]